Modulation of calcium-dependent inactivation of L-type Ca2+ channels via β-adrenergic signaling in thalamocortical relay neurons. - Vladan Rankovic (Public Library of Science (PLoS), 2011)
Neuronal high-voltage-activated (HVA) Ca(2+) channels are rapidly inactivated by a mechanism that is termed Ca(2+)-dependent inactivation (CDI). In this study we have shown that β-adrenergic receptor (βAR) stimulation inhibits CDI in rat thalamocortical (TC) relay neurons. This effect can be blocked by inhibition of cAMP-dependent protein kinase (PKA) with a cell-permeable inhibitor (myristoylated protein kinase inhibitor-(14-22)-amide) or A-kinase anchor protein (AKAP) St-Ht31 inhibitory peptide, suggesting a critical role of these molecules downstream of the receptor. Moreover, inhibition of protein phosphatases (PP) with okadaic acid revealed the involvement of phosphorylation events in modulation of CDI after βAR stimulation. Double fluorescence immunocytochemistry and pull down experiments further support the idea that modulation of CDI in TC neurons via βAR stimulation requires a protein complex consisting of Ca(V)1.2, PKA and proteins from the AKAP family. All together our data suggest that AKAPs mediate targeting of PKA to L-type Ca(2+) channels allowing their phosphorylation and thereby modulation of CDI.